Resposta :
Resposta: Olá,Tudo Bem?
a)3x + 128 = 4x - 340
3x - 4x + 128 = - 340
3x - 4x = - 340 - 128
- x = - 340 - 128
- x = - 468
x = 468
b)x + 2 = 83x - 15
x - 83x - 2 = - 15
x - 83x = - 15 + 2
- 82x = - 15 + 2
- 82x = - 13
x = 13
82
c)8x - 78 = x + 19
8x - x - 78 = 19
8x - x = 19 + 78
7x = 19 + 78
7x = 97
x = 97
7
d)52x + 17 = 23x - 45
52x - 23x + 17 = - 45
52x - 23x = - 45 - 17
29x = - 45 - 17
29x = - 62
x = - 62
29
Explicação:
Espero ter ajudado :)
![Ver imagem MAYLTON5151](https://pt-static.z-dn.net/files/d60/9e56e73b337040a2773fee842bb1cd78.jpg)
![Ver imagem MAYLTON5151](https://pt-static.z-dn.net/files/dcd/60cc31d463d31d7840199b426a5b283d.jpg)
![Ver imagem MAYLTON5151](https://pt-static.z-dn.net/files/d00/8de0fbbee55520227729cca90b829fba.jpg)
![Ver imagem MAYLTON5151](https://pt-static.z-dn.net/files/dd3/188d4fc4626f03dd32e0a191150126e0.jpg)